Training intensity distribution over a four-year cycle in Olympic champion rowers: Different roads lead to Rio - Plews, D. J.; Laursen, P. B. (2017)
The purpose of this study was to compare the training intensity distribution (TID) of the undefeated world champion male rowing New Zealand (kiwi)pair over a four-year Olympic cycle, across training phases, training years, and between individuals. Training data, including heart rate and boat speed, were recorded in the athletes rowing in the same boat between March 2013 and August 2016, ending with the Rio Olympics final. Progressive exercise tests assessed first (LT1) and second (LT2) lactate thresholds and associated heart rates, to determine the percentage of training performed below, between and above these demarcation points. Training an average of only 12-15 h/wk throughout the Olympic cycle, the mean percent distribution of time (±SD) at each training intensity was 80.4 ± 5.5% <LT1, 17.9 ± 5.3% LT1-LT2and 1.8 ± 0.8% >LT2 for Rower A and 67.3 ± 9.0% <LT1, 30.2 ± 9.4% LT1-LT2, and 2.4 ± 1.4% >LT2for Rower B. Across the years 2014-2016, Rower A performed most likelymore training <LT1, while Rower B performed mostly likely more training between LT1-LT2. Training appeared to become more polarised, with greater amounts of time spent <LT1, with increased training duration (R=0.38-0.43). Two of the world`s best rowers, rowing together in the same boat with an undefeated record across an Olympic cycle, travelled markedly different "roads to Rio" within the context of their TID, with one rower displaying a polarised model of TID, and the other pyramidal. However, TID trended towards becoming more polarised in both rowers with increased training duration.